The Influence of Social Media Marketing, Word of Mouth, Brand Awareness on Purchase Decision Through Bursa Coffee Consumer Satisfaction - Herkamilan, Verdi; Sutiono, Heru Tri; Yudhiantoro, Danang (UPN Veteran Yogyakarta, 2024)
This research aims to explore the direct and indirect effects of social media marketing, word of mouth, and brand awareness on purchase decisions through consumer satisfaction at Bursa Coffee in Sleman city. The study employs a quantitative approach with the population being all Bursa Coffee consumers in Sleman. The sample collected in the Sleman area was 163 respondents. A questionnaire was utilized to collect data from 163 respondents aged 20-25, encompassing both genders and educational backgrounds from high school to postgraduate levels. Also work backgrounds. Monthly expenditures ranged from Rp100,000 to Rp500,000, and monthly visits varied from 1 to more than 3 times. The data analysis technique employed in this research is Partial Least Square (PLS). Results reveal that social media marketing, word of mouth, and brand awareness significantly and positively influence purchase decisions. Additionally, these factors positively impact consumer satisfaction, and consumer satisfaction, in turn, positively affects purchase decisions. The study indicates that social media marketing, word of mouth, and brand awareness collectively influence purchase decisions through the mediator of consumer satisfaction.